Analisis Sikap Tanggung Jawab Siswa dalam Proses Pembelajaran Daring Melalui Aplikasi Whatsapp - Rohmatus Syafi'ah; Wahyu Sari (Universitas Islam Lamongan, 2020)
Abstract: On the covid-19 pandemic, all of the education systems are conducted online. In online learning, the 4th-grade students of SDN Tegalrejo Tulungagung use Whatsapp. Online learning using Whatsapp refers to the 2013 curriculum, which is several sub-theme into a theme. The 2013 curriculum has some attitudes which are needed to learn. One of them is a responsible attitude. This study's responsibility attitude consists of two indicators: 1) fulfill its obligations, and 2) self-discipline. This research was conducted in grade 4 SD Negeri Tegalrejo Tulungagung. The research design in this study was qualitative research with a descriptive system. The data collecting method of this study were questionnaire, interview, and documentation. Data analysis in this study used transcripts of the results of questionnaires and interviews, data reduction, data interpretation, and triangulation. This study's work from students' questionnaire shown students' responsibility attitude in online learning using WhatsApp on Theme 9 Sub-theme 3 Lesson 3 get a percentage of 91%; it is classified as